PENGGUNAAN KOMBINASI KADAR PROTEIN PAKAN DAN THREONIN TERHADAP PENAMPILAN PRODUKSI DAN KECERNAAN PAKAN PADA AYAM KAMPUNG UNGGUL - Santoso, Erik Priyo; Fitasari, Eka; Togola, Veronika; Leuhapu, Robertus Aba (BUANA SAINS, 2023)
This research aimed to determine the effect of a combination of feed protein levels and threonine, namely feed formulations with crude protein (PK) levels of 19%, 18%, and 17% combined with the addition of the amino acid threonine 100%, 110%, and 120%. The research used a Completely Randomized Design Method repeated three times. The parameters measured in this study were production performance (feed consumption, body weight gain, FCR, feed efficiency) and digestibility (metabolic energy and N retention). The combination of feed PK and threonine content did not significantly affect all parameters (p0.05). Feed PK significantly affected feed consumption, FCR value, and N retention value. The results showed that the highest body weight gain was in 80-day-old chickens produced in the 18% PK treatment 1264.43 gr/head and decreased in the 17% CP treatment. The highest feed efficiency occurred in the PK 18% treatment at 34.99%. The 18% protein at all threonine levels gave an AMEn value with an average value of 3418.15 Kcal/kg and N Retention with a value of 89.12%. Feed treatment with a protein content of 18% combined with 100%, 110%, and 120% threonine treatment gave the best results in body weight gain and feed efficiency.